Tramadol utilization among patients with higher risk of adverse drug events: A claims analysis of commercially insured and Medicare Advantage members - Borrelli, PhD, PharmD, MBA, Eric P.; Bratberg, PharmD, FAPhA, Jeffrey; Greaney, PhD, MPH, Mary L.; Kogut, PhD, MBA, RPh, Stephen J. (Journal of Opioid Management, 2023)
Objective: To assess prescribing of tramadol among patients with contraindications and higher risks of adverse events in a large population of commercially insured and Medicare Advantage members. Design: We performed a cross-sectional analysis evaluating tramadol utilization in patients with higher risk of adverse outcomes. Setting: This study utilized 2016-2017 data from the Optum Clinformatics Data Mart. Patients and participants: Patients with at least one tramadol prescription without a cancer or sickle cell diagnosis during the study period. Main outcome measures: We first determined if tramadol was prescribed among patients with contraindications or risk factors for adverse outcomes. We then determined if patient demographic or clinical factors were associated with the use of tramadol in these higher-risk scenarios using multivariable logistic regression models. Results: Among patients with at least one prescription for tramadol, 19.66 percent (99 percent CI: 19.57-19.75) concurrently received an interacting cytochrome P450 isoenzyme medication, 19.24 percent (99 percent CI: 19.15-19.33) concurrently received a serotonergic medication, and 7.93 percent (99 percent CI: 7.88-8.00) concurrently received a benzodiazepine. Additionally, 1.59 percent (99 percent CI: 1.56-1.61) of patients who received tramadol also had a seizure disorder, while 0.55 percent (99 percent CI: 0.53-0.56) of patients were under the age of 18. Overall, nearly one in three patients (31.17 percent) received tramadol in the presence of at least one of these risks (99 percent CI: 31.06-31.27). Conclusion: Almost one in three patients prescribed tramadol had a clinically significant drug interaction or contraindication for use, suggesting that prescribers often disregard these concerns. Real-world studies are needed to better understand the likelihood of harms associated with the use of tramadol in these contexts.